Prevalence and structural protein encoding gene sequence (VP) of porcine parvovirus 2 (PPV2) in slaughtered pigs in Central provinces of Vietnam - Nguyen, Tran Trung; Tran , Quoc Dung; Nguyen, Thi Dieu Thuy (Hue University Journal of Science: Natural Science, 2023)
Porcine parvovirus (PPV) is a DNA virus and causative agent of several reproductive problems in sows. This study was conducted to determine the prevalence and analyze the DNA sequence of structural protein encoding gene (VP) of PPV2 genotype in pigs. A total of 146 samples (lung and blood samples) were collected from slaughtered pigs of seven provinces in Central Vietnam during 2018-2019. The overall prevalence of PPV2 was 56.2% (82/146). PPV2 positive rate in each province ranged from 37.5% for Quang Nam to 100% for Quang Binh, with the exception of Da Nang, where no PPV2 positive samples were detected. Nearly complete PPV2-VP gene sequences of three strains were identified with the length of 2,493 nucleotides and deposited in GenBank with accession numbers of OL913365-OL913367. Four nucleotide substitutions were detected in Vietnamese PPV2 isolates and were not observed in PPV2 reference strains. Multiple alignment and comparison of nucleotide and deduced amino acid sequences showed the high similarity within Vietnamese PPV2 strains (95.6-96.5% and 94.7-96.9%, respectively). The PPV2 strains from this study clustered together with the "primitive" PPV2 strains from Myanmar, and strains from China in a main clade in the phylogenetic tree (Cluster A). This is the first report on the prevalence of PPV2 genotype and its VP gene sequence in pigs in Vietnam. This also provides the valuable information on the molecular evolution of locally circulating PPV2 and contributes to the control of PPV-induced SMEDI syndrome in sows, especially in the central provinces of Vietnam.